Genetic Groups of Fine-Aroma Native Cacao Based on Morphological and Sensory Descriptors in Northeast Peru - Oliva-Cruz, Manuel; Goñas, Malluri; Bobadilla, Leidy G.; Rubio, Karol B.; Escobedo-Ocampo, Patricia; García Rosero, Ligia M.; Rojas Briceño, Nilton B.; Maicelo-Quintana, Jorge L. (Frontiers in Plant Science, 2022)
The northeastern region of Peru is one of the centers of origin of cocoa due to the great diversity of this cultivar. The objective of this study is, therefore, to search for different genetic groups of 146 ecotypes of fine-aroma native cocoa from the northeastern region of Peru, based on the morphological descriptors of pods, seeds, sensory, yield and sampling altitude. The data were analyzed using multivariate statistics; a cluster analysis was performed with the numerical and categorical variables, followed by a Principal Component Analysis (PCA) and the DGC (Di Rienzo, Guzmán y Casanoves) mean comparison test for the numerical data. Contingency tables and a Multiple Correspondence Analysis (MCA) were performed for the categorical data. We differentiated 5 genetic groups; helpfully, sensory characteristics of the flowers and pod, size and weight of the seeds and pod index were in fact crucial in separating the groups. The ecotypes of the groups labelled as '' Indes'' and ''Bagüinos'' reported the best sensory characteristics with high floral and fruity notes and with a good yield expressed in Pod Index: 13.88 and 11.88 respectively; furthermore, these ecotypes are found at medium and high altitudes, above 500 m a.s.l., a factor that enables them to express their sensory and yield attributes. On the other hand, the ecotypes known as ''Toribianos'' and ''Cajas'' report the highest pod indices (20.77 and 16.78 respectively), resulting in low productivity. In the future, the variability of the ecotypes found will help establish genetic improvement programmes that contribute to the development of cocoa farming in general.